Analisis Kegiatan Penyediaan Berkas Rekam Medis Rawat Inap di RSU Haji Surabaya - Novita Yuken Nur Aulia; Novita Nuraini; Rossalina Adi Wijayanti (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
One indicator in measuring the quality of medical records is the punctuality. The punctuality means managing the medical record file from the patient registering until the medical record file with the time limit specified in the standard operating procedure. At Haji Hospital Surabaya, the delay in providing theÂ  inpatient medical records is still a problem. It can cause obstruction of the patient care process so that it will also affect service satisfaction. This research was aimed to analyze the activities of providing inpatient medical records at the Hajj General Hospital in Surabaya with the type of qualitative research. Data collection techniques used are observation, interviews, and documentation based on the variables Ability, Motivation, and Opportunities. The results of this study indicate that there are no SOPs related to the time the provision of inpatient medical records is the main factor being addressed. The Efforts can be made by rearranging SPOs related to providing inpatient medical record time.